RNAseq-derived Read Counts for Primary and Locally Recurring Breast Cancers - de Marchi, Tommaso (Lund University, 2023)
Read counts from RNAseq analysis for all 75 breast cancer samples included in the study "Proteogenomics decodes the evolution of human ipsilateral breast cancer". De Marchi T, Pyl PT, Sjöström M, Reinsbach SE, DiLorenzo S, Nystedt B, Tran L, Pekar G, Wärnberg F, Fredriksson I, Malmström P, Fernö M, Malmström L, Malmström J, Nimèus E.

"RNA.RAW.COUNTS" for all genes are reported here. "RNA.SCALED.COUNTS" report on filtered (for missing data) reads with matching Uniprot/swissprot identifier. Reads were then scaled and centered across samples and genes.

This dataset was used for Figure 3 in the following manuscript:

"Proteogenomics decodes the evolution of human ipsilateral breast cancer". De Marchi T, Pyl PT, Sjöström M, Reinsbach SE, DiLorenzo S, Nystedt B, Tran L, Pekar G, Wärnberg F, Fredriksson I, Malmström P, Fernö M, Malmström L, Malmström J, Nimèus E. accepted for publication
Keywords: Genomics and transcriptomics; Proteomics and metabolomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik